PENGARUH LATAR BELAKANG PENDIDIKAN DAN PELATIHAN TERHADAP KINERJA ACCOUNT OFFICER (AO) KREDIT KOMERSIAL BANK BRI SUMATERA BARAT - Dini, Ega Sri; Sari, Mareta Kemala; Amaluis, Dina (Pendidikan Ekonomi, 2013)
AbstrakÂ This study aims to reveal the effect of: educational background and training of employees kierja account officer (AO) BRI Bank of West Sumatra.Type of research conducted in this research is descriptive quantitative. The population is the total number of employees accounts officer (AO) Bank BRI Sumatra were 30. Sampling technique in this research is to use the total sampling where respondents were less than 100 then all the population sampled.Data were collected through a questionnaire using a Likert scale that has been tested validity and reliability. The data analysis technique used is descriptive analysis. To test the hypothesis used t test and f. Based on the results of t-test of hypothesis testing is not educational background and significant positive effect on employee performance, training t-test positive and significant impact on employee performance. While testing the influence of f together positive and significant correlation between educational background and pelaihan on employee performance. The amount of influence the educational background and training on employee performance is 32.90% and the remaining 67.10% is influenced by other variables not included in the research model.Â Keywords: Educational Background, Training and Employee Performance